Electrical performances of pre-production staves for the ATLAS ITk Strip Detector Upgrade. (1st January 2023) - Capocasa, F.; Gutierrez Zagazeta, L.F.; Lynn, D.; Phillips, P.W.; Stucci, S.A.; Tricoli, A.; Van Nieuwenhuizen, G.
Abstract: The ATLAS experiment is currently preparing for an upgrade of the inner tracking detector for the High-Luminosity LHC. The new tracker, ITk, employs an all-silicon detector with outer strip layers. The building block of the ITk strip barrel is the stave which consists of a low-mass support structure hosting the common electrical, optical and cooling services as well as 28 silicon modules. In this contribution, we outline the challenging aspects of the stave pre-production testing phase at Brookhaven National Laboratory. The electrical characterization of these staves, hosting the final design of all ASICs, will be discussed in detail.